Dasar-Dasar Pendidikan Islam dalam Al-Qur’an - Al Firdaus (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2024)
The basis of Islamic education plays a vital role in the future of the Indonesian nation. There is still homework that scholars need to complete regarding this training. The decline in the work enthusiasm of Indonesian children is apparent. The Koran has been related to every event that has occurred since it was revealed. Islamic education aims to illuminate the dark side of human behavior. Oh, that's why humans are ordered to read events in this universe to give a signal that humans without knowledge and revelation will lead to destruction. So it is important to deepen the study of the basics of education in the Al-Qur'an so that the Al-Qur'an can provide updates to the world of education. The method used in the study is descriptive analysis combined with Maudhu'i interpretation. Meanwhile, the data obtained through library research uses three stages of description, comparison, analysis, and development, which ultimately results in a conclusion by the problem formulation and research objectives.